2016
DOI: 10.1177/0192513x16680013
|View full text |Cite
|
Sign up to set email alerts
|

Sharing the Caring: Attitude–Behavior Discrepancies and Partnership Dynamics

Abstract: Even though ideals in favor of gender equality in the private sphere are wide spread, discrepancies between ideals and actual behavior are common. Such discrepancies and potential dissatisfaction with gender unequal behavior within a couple are expected to influence partnership dynamics negatively. This study examines how discrepancies between the perceived ideal sharing of parental leave and the actual division of leave, as well as satisfaction with the division are associated with (a) relationship satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…However, most associations (15) between the independent variables and child outcomes were positive. However, a positive association again seems dependent on country (Brodmann et al 2007;Cooke 2009), women's employment (Cooke 2009;Schober 2013;Nagase and Brinton 2017), parity-specific outcomes (Mencarini and Tanturri 2004;Nilsson 2010;Komatsu 2011;Goldscheider et al 2013;Schober 2013;Aassve et al 2015;Miettinen et al 2015), the importance of childcare rather than housework division (Cooke 2004;Mencarini and Tanturri 2004;Miettinen et al 2015;Dommermuth et al 2017), and gender-for men but not women (Kaufman 2000;Bernhardt and Goldscheider 2006;Brandén et al 2018) or vice versa (Goldscheider et al 2013;Aassve et al 2015), and year (Zhou and Kan 2019). The significance of ideal over actual division of labour in determining higher fertility outcomes is evident (Alonso 2004;Torr and Short 2004;Luppi 2016), although one Australian study finds the opposite (Craig and Siminski 2010).…”
Section: Figurementioning
confidence: 99%
“…However, most associations (15) between the independent variables and child outcomes were positive. However, a positive association again seems dependent on country (Brodmann et al 2007;Cooke 2009), women's employment (Cooke 2009;Schober 2013;Nagase and Brinton 2017), parity-specific outcomes (Mencarini and Tanturri 2004;Nilsson 2010;Komatsu 2011;Goldscheider et al 2013;Schober 2013;Aassve et al 2015;Miettinen et al 2015), the importance of childcare rather than housework division (Cooke 2004;Mencarini and Tanturri 2004;Miettinen et al 2015;Dommermuth et al 2017), and gender-for men but not women (Kaufman 2000;Bernhardt and Goldscheider 2006;Brandén et al 2018) or vice versa (Goldscheider et al 2013;Aassve et al 2015), and year (Zhou and Kan 2019). The significance of ideal over actual division of labour in determining higher fertility outcomes is evident (Alonso 2004;Torr and Short 2004;Luppi 2016), although one Australian study finds the opposite (Craig and Siminski 2010).…”
Section: Figurementioning
confidence: 99%
“…The small change may be reflective of the fact that most of the transition‐to‐parenthood relationship change may have already occurred from pre‐birth to post‐birth (Mitnick et al ., 2009). The finding is supported by previous Swedish research on fathers’ satisfaction with how much parental leave they used and with their relationship (Brandén et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Factors that have been acknowledged as important for the parental leave allocation are economic considerations and work life factors, although gender has been found to be the most influential determinant of parental leave division (Almqvist et al ., 2011). Our finding that mothers did not differ in their perception of their couple relationship is consistent with previous Swedish research, which also did not find any significant association between mothers’ (dis)satisfaction with their division of parental leave and relationship satisfaction (Brandén et al ., 2016). Future studies are needed to replicate the study findings and explore the mechanism underlying the link found in fathers, but not in mothers, between parental leave division and change in perceived couple relationship quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unequal division of household labour often affects women's labour force participation and earnings (Antonopoulos & Hirwar, 2010;Organisation for Economic Co-operation and Development, 2012). Likewise, women are more likely to experience higher levels of exhaustion, depression and stress due to unequal division of household labour (Bird, 1999;Branden, Duvander & Ohlsson-Wijk, 2016;Lively, Steelman & Powell, 2010;Zimmerman, 2000).…”
Section: Introductionmentioning
confidence: 99%